Successful team-based development of an online course with an external partner: An analysis of the perspectives of academics - Croxford, Sharon; Thomas, Colleen; Horvath, Deanna; Buultjens, Melissa; Stirling, Emma; Larsen, Amy; Roman Stasis, Tania; Radcliffe, Jessica; Buultjens, Phil; McDonald, Stuart; Forsyth, Adrienne (Journal of University Teaching and Learning Practice, 2019)
Course and subject development teams are increasingly seen in the tertiary online teaching environment and they face a unique set of challenges. The purpose of this study was to synthesise and share learnings of 12 academics involved in the development of subjects with an external partner for a new multidisciplinary online health science course at an Australian university, in order to improve ongoing development within the course and inform new course development. In this case study, thematic analysis of focus group discussions and qualitative survey data identified five key themes related to the development process: time management, setting expectations, communication, the development team, and ownership. Barriers to productive subject development included unrealistic timelines, unclear lines of communication, unmet or unrealistic expectations and lack of recognition of team members’ expertise, and lack of support for genuine collaboration. Team-based development of an online course has the potential to be a rewarding experience for academics. In order for the benefits to be realised, approaches to development underpinned by a community-centred framework, observing core values such as collaboration, shared sense of purpose and expectations, would address a number of the issues identified in this study.